Logística internacional de la exportación de café Colombiano a Alemania (2019)
The present work focuses on determining the international logistics of exporting Colombian coffee to Germany, from its origin to its final port destination. Therefore, the development of this research began with the interviews to coffee growers, about the way in which it is exported, whether roasted or green, the type of packaging and the amount of kilograms in each package, how and where it is transported, what care must be taken for transportation, what port is embarked for export, what requirements are needed, and also the costs that must be taken into account for export, all the necessary logistics from the origin to its final destination, in this case, Germany. As a result, it was possible to determine the international logistics for the export of Colombian coffee to Germany. Above all, giving a range of costs so that a coffee grower can have an idea of what it can cost national and international transport, taking into account necessary documents, times, modes and forms of packaging and more importantly, the necessary care to coffee and its properties.